2015
DOI: 10.1007/s00405-015-3651-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of PET/CT in the management of patients affected by head and neck tumors: a review of the literature

Abstract: The management of head and neck tumor (HNSCC) has been changing over the years, especially due to the aid of imaging techniques that help physicians to attain a correct diagnosis. These techniques represent a valuable tool to help tailor treatment and during follow-up of patients affected by malignancies. The aim of this review is to summarize the results of the most recent and relevant studies about the use of PET imaging in HNSCCs. This review is divided into six chapters: (1) The role of PET/CT in the pre-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 137 publications
0
12
0
Order By: Relevance
“…[4][5][6][7][8][9][10][11] An important advantage of PET/CT is that a whole-body scan allows for the detection of distant metastases and unexpected secondary cancers. Positron emission tomography (PET) and, in particular, combined PET-computed tomography (PET/CT) have become popular as useful diagnostic and prognostic tools for pretreatment staging, radiotherapy planning, measuring treatment response for residual or recurrent disease, and monitoring posttreatment follow-up results in various head and neck malignancies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7][8][9][10][11] An important advantage of PET/CT is that a whole-body scan allows for the detection of distant metastases and unexpected secondary cancers. Positron emission tomography (PET) and, in particular, combined PET-computed tomography (PET/CT) have become popular as useful diagnostic and prognostic tools for pretreatment staging, radiotherapy planning, measuring treatment response for residual or recurrent disease, and monitoring posttreatment follow-up results in various head and neck malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…residual or recurrent disease, and monitoring posttreatment follow-up results in various head and neck malignancies. [4][5][6][7][8][9][10][11] An important advantage of PET/CT is that a whole-body scan allows for the detection of distant metastases and unexpected secondary cancers. The National Comprehensive Cancer Network (NCCN) Clinical Practice Guidelines in Oncology for head and neck cancers have been updated to include PET/CT as a supplement to the clinical evaluation in the posttreatment surveillance of head and neck squamous cell carcinoma (HNSCC) patients.…”
mentioning
confidence: 99%
“…The assessment of tumour hypoxia is an important issue in clinical management in HNC as patients with hypoxic tumours generally have poorer outcome, show resistance to conventional treatment and could be treated selectively with tailored treatments [11]. Specific treatment may include the use of tirapazamine (and hypoxiaselective cytotoxin), radiosensitizers (e.g.…”
Section: Hypoxiamentioning
confidence: 99%
“…Parameters frequently used in analysis with FDG-PET examinations are the maximum standard uptake value (SUVmax), SUVmean, metabolic tumor volume (MTV), and total lesion glycolysis (TLG). [5][6][7] Some studies noted the effectiveness of SUVmax, which is the most commonly used parameter in PET examinations, 8,9 whereas other studies showed that SUVmax had no significance as a predictor of prognosis in patients with head and neck tumors. 10,11 Thus, it can be thought that the utility of SUVmax as a predictor of prognosis in head and neck tumors is still controversial.…”
Section: Introductionmentioning
confidence: 99%